2010
DOI: 10.1590/s1415-52732010000600006
|View full text |Cite
|
Sign up to set email alerts
|

Consumo alimentar de escolares das redes pública e privada de ensino em São Luís, Maranhão

Abstract: OBJETIVO: Avaliar o consumo alimentar de 570 escolares de 9 a 16 anos das redes pública e privada de ensino, em São Luís (MA), matriculados da 4ª à 8ª séries, em 2005. MÉTODOS: Os dados de consumo alimentar foram coletados por meio de Inquérito Alimentar Recordatório de 24 horas. O consumo de energia, macronutrientes, vitamina A, vitamina C, ferro e cálcio foram comparados às Dietary Reference Intakes. Considerou-se o número de vezes em que os alimentos apareceram na dieta e o seu agrupamento foi feito de acor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 22 publications
4
11
0
20
Order By: Relevance
“…Similar results were observed in a study 38 analyzing the dietary intake of public and private schoolchildren in São Luís, Brazil. The foods consumed the most were rice (97.6%), bread (77.6%), beans (61.6%), butter/margarine (61.1%), and beef (59.6%).…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were observed in a study 38 analyzing the dietary intake of public and private schoolchildren in São Luís, Brazil. The foods consumed the most were rice (97.6%), bread (77.6%), beans (61.6%), butter/margarine (61.1%), and beef (59.6%).…”
Section: Discussionsupporting
confidence: 89%
“…However, drastic changes in the population morbidity and mortality profile and behavior of Brazilian youth have not occurred since CVD are still the leading cause of death in Brazil 2 and recent studies continue to report the low quality diet of children and adolescents 27,28 , thus ensuring the quality of the conclusions of this research.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies conducted in different countries, including Brazil, have shown conflicting results regarding the association between excessive consumption of sugar-rich food products by adolescents and gender, age and type of school 5,7,9,18,19 . On the other hand, aspects such as nutritional status, the habit of eating while watching TV, time spent watching TV, the availability of such foods at school or at home, inadequate eating habits among family and friends, and having meals with parents are more consistently associated with consumption of these foods 5,7,18,20 .…”
Section: Introductionmentioning
confidence: 99%